2020
DOI: 10.3390/en13174360
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling and Performance Evaluation of Standing Wave Thermoacoustic Refrigerators with a Multi-Layered Stack

Abstract: Thermoacoustic refrigerators have huge potential to replace conventional refrigeration systems as an alternative clean refrigeration technology. These devices utilize conversion of acoustic power and heat energy to generate the desired cooling. The stack plays a pivotal role in the performance of Standing Wave Thermoacoustic Refrigerators (SWTARs), as the heat transfer takes place across it. Performance of stacks can be significantly improved by making an arrangement of different materials inside the stack, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For the model, the study used a 2D axisymmetric model, conjugate heat transfer, laminar flow coupled by nonisothermal flow multiphysics. The type of fluid flow used was determined by calculating the Reynolds number (๐‘…๐‘… ๐‘’๐‘’ ), which referred to as the critical Reynolds number limited to 2300, (๐‘…๐‘… ๐‘’๐‘’๐‘’๐‘’๐‘’๐‘’ = 2๐‘ข๐‘ข 1 /โˆš๐‘‰๐‘‰๐œ”๐œ” ) [19]. A time-dependant solution option was utilised.…”
Section: Numerical Methodologies and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the model, the study used a 2D axisymmetric model, conjugate heat transfer, laminar flow coupled by nonisothermal flow multiphysics. The type of fluid flow used was determined by calculating the Reynolds number (๐‘…๐‘… ๐‘’๐‘’ ), which referred to as the critical Reynolds number limited to 2300, (๐‘…๐‘… ๐‘’๐‘’๐‘’๐‘’๐‘’๐‘’ = 2๐‘ข๐‘ข 1 /โˆš๐‘‰๐‘‰๐œ”๐œ” ) [19]. A time-dependant solution option was utilised.…”
Section: Numerical Methodologies and Boundary Conditionsmentioning
confidence: 99%
“…In a study by Bhatti et al (2020), they compared homogeneous stacks using Celcor and Kapton to multi-layered stacks combining Celcor and RVC, and Kapton with RVC. In the multi-layered stacks, they found a temperature increase of up to 26.14%, an 8.5% enhancement in COP (Coefficient of Performance), and a 4.55% reduction in energy consumption.…”
Section: Stack Materialsmentioning
confidence: 99%
“…Additionally, the ANSYS software has numerous applications in other fields. ANSYS software was used by Bhatti et al [32] to numerically model and evaluate the performance of a standing-wave thermoacoustic refrigerator with multiple stacks. The ANSYS Fluent software package was used by Hamdamov et al [33] to conduct mathematical modeling of vertical axis wind turbines.…”
Section: Introductionmentioning
confidence: 99%
“…A bulk porous media representing stack in a thermoacoustic systems, such as RVC foams, were analytically studied by Tasnim et al [29]. Bhatti et al [30], in turn, numerically investigated the multi-layered stacks, that are composed of different materials. Their results showed that multi-layered stacks consume less energy and provide higher COP than their homogeneous counterparts.…”
Section: Introductionmentioning
confidence: 99%